How It Ends - Lo, Catherine (Boston : Houghton Mifflin Harcourt, 2016)
Jessica is a good student who hates school because she is bullied by the "cool" girls and she is startled and grateful when Annie, the new girl in her southern Ontario high school, seeks her out on the first day of tenth grade and defends her from the bullying--it is a friendship that both girls need, but one based on assumptions and misunderstandings that ultimately threaten to drive them apart.
When new girl Annie befriends Jessica on the first day of tenth grade and defends her from bullying, they begin a friendship that both girls need, but it is one based on assumptions and misunderstandings that ultimately threaten to drive them apart.
Keywords: Best friends -- Juvenile fiction; Bullying -- Juvenile fiction; Miscommunication -- Juvenile fiction; Families -- Ontario; Juvenile fiction; Dating (Social customs) -- Juvenile fiction; High schools -- Ontario; Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Bullying -- Fiction; Miscommunication -- Fiction; Family life -- Ontario; Fiction; Dating (Social customs) -- Fiction; High schools -- Fiction; Schools -- Fiction; Ontario. -- Juvenile fiction; Canada. -- Fiction; Young Adult Fiction